Studi Peran Film dalam Dunia Pendidikan - Muslih Aris Handayani (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Delivering lesson is one of verbal communication forms, where teacher or lecturer submits the lesson items to audients (students). Target of communications is deliver the thought or message from someone to others. In order to message can arrive to target we need the existence of channel. Film as one of message’s delivering equipment from producer and director have big influence to audiences. Film also partakes to give contribution in education development. Film represents media that have great ability in assisting learning process. From this study we can conclude that, firstly, film represent one of the media type able to be exploited to delivering Iesson items. Secondly, among film benefit in education, for example can bring the student enthusiasm, because its excellent quality in color, movement and voice; can motivate the child to learn, etc. Thirdly, film gives the high persuasive level to Iesson items. Fourth, for the purpose of study, film has to design according to student condition.